The study on liver function derangements in association with severity and bleeding outcome in dengue fever - Fariz Safhan, Mohamad Nor (2008)
Dengue fever is an endemic infective disease which has seen a significant re-emergence in Malaysia. Liver function derangements have been desctibed in dengue infection but its association with bleeding occurrence has not been consistently shown in previous studies. Objectives The main objective was to study the association between liver function derangements and the severity of dengue virus infection and bleeding outcomes. Methodology This is a cross-sectional study involving 144 patients with dengue virus infection (World Health Organisation criteria) recruited from October 2005 until March 2006 in Hospital Tengku Ampuan Afzan, Kuantan. Severity of dengue infection was classified into uncomplicated dengue fever (DF) and dengue haemmThagic fever (DHF) with or without Dengue Shock Syndrome (DSS). The bleeding outcomes were grouped into "no bleeding", "petechiae", "minor bleeding" and "major bleeding". The association between liver derangement and DHF was analysed using independent t-test and multiple logistic regression analysis. The association between liver derangement and bleeding outcome was analysed using Kruskal-Wallis and Mann-Whitney tests. XII Results The mean patient's age was 31 ± 12 years old. There were 85 (59.7%) patients with DHF. There were 31 (21.5%) patients who had no bleeding, 39 (27.1 %) patients had petechiae, 53 (36.8%) patients had minor bleeding and 21 (14.6%) patients had major bleeding. The mean AST level in DHF was 253.5 ± 205.5 IU/L (p<O.OOI), mean ALT level in DHF was 171.1 ± 185.2 IU/L (p < 0.001), mean albumin level in DHF was 32.0 ± 5.7 IU/L (p < 0.001), mean ALP level in DHF was 97.6 ± 48.9 J.tmol/L (p = 0.027) and mean direct bilimbin level in DHF was 6.2 + 5.4 (p < 0.00 I). Multiple logistic regression analysis showed that AST (OR 1.025, p < 0.001, 95% C.l. 1.014- 1.036), as well as abdominal pain and plasma leakage were significantly associated with DHF. Bleeding outcome was associated with the derangement of AST, AL T, albumin (p<O.OO I) and direct bilimbin (p = 0.038) but not with ALP (p=0.585) and INR (p=0.593). Conclusion The study showed that a significant association existed between liver function derangements, predominantly AST with DHF and bleeding outcome. AST can be a useful surrogate marker to predict disease severity and bleeding outcome in dengue infection.